2017
DOI: 10.1051/0004-6361/201630308
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared HD emission as a measure of protoplanetary disk mass

Abstract: Context. Protoplanetary disks around young stars are the sites of planet formation. While the dust mass can be estimated using standard methods, determining the gas mass -and thus the amount of material available to form giant planets -has proven to be very difficult. Hydrogen deuteride (HD) is a promising alternative to the commonly-used gas mass tracer, carbon monoxide. However, its potential has not yet been investigated with models incorporating both HD and CO isotopologue-specific chemistry, and its sensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(165 citation statements)
references
References 53 publications
(131 reference statements)
14
150
1
Order By: Relevance
“…This system is the closest known protoplanetary disc to us (60.2 AU, Gaia Collaboration et al 2018), with a central star of 0.7-0.8 M (Andrews et al 2012;Herczeg & Hillenbrand 2014) relatively old (7-10 Myr, Ruane et al 2017), and with an estimated total disc mass of 0.05 M (Bergin et al 2013). The surface gas density has been modelled from ALMA line emission observations (Kama et al 2016;Trapman et al 2017). From their unperturbed models, we used a fiducial surface density of 10.9 g · cm −2 at 40 AU for the re-scaling (a surface density factor ×0.24 of the simulated disc).…”
Section: Tw Hyamentioning
confidence: 99%
“…This system is the closest known protoplanetary disc to us (60.2 AU, Gaia Collaboration et al 2018), with a central star of 0.7-0.8 M (Andrews et al 2012;Herczeg & Hillenbrand 2014) relatively old (7-10 Myr, Ruane et al 2017), and with an estimated total disc mass of 0.05 M (Bergin et al 2013). The surface gas density has been modelled from ALMA line emission observations (Kama et al 2016;Trapman et al 2017). From their unperturbed models, we used a fiducial surface density of 10.9 g · cm −2 at 40 AU for the re-scaling (a surface density factor ×0.24 of the simulated disc).…”
Section: Tw Hyamentioning
confidence: 99%
“…Modelling of the HD J = 1 − 0 transition, Bergin et al (2013) concluded that the mass of the disk must be M disk > 0.05 M sun . More recently, Trapman et al (2017) used additional observations of the J = 2 − 1 transition to find a mass of between 6 × 10 −3 and 9 × 10 −3 M sun . This large range is due primarily to the sensitivity of the HD emission to the assumed thermal structure and differences in assumed the cosmic D/H ratio.…”
Section: Minimum Disk Massmentioning
confidence: 99%
“…At this mass the self-gravity of the disc is significant and gravitational instability may lead to disc fragmentation (Kratter & Lodato 2016). Trapman et al (2017), using additional constraints on the vertical structure from Kama et al (2016) and adding HD 2-1 line observations, suggest a gas mass, in daniel.mentiplay@monash.edu between these two extremes, of (6-9) × 10 −3 M . Recent carbon sulfide (CS) molecular observations find a minimum disc mass of 3 × 10 −4 M (Teague et al 2018).…”
Section: Introductionmentioning
confidence: 97%